Pengaruh Penambahan Serbuk Kayu Dan Bestmittel Pada Campuran Beton Terhadap Workability Dan Kuat Tekan - Senni Fatriani; Fathoni Usman; Debby Sinta Devi (Jurnal Konstruksi, 2026)
Concrete is a composite material widely used due to its high compressive strength and resistance to structural loads. Environmentally friendly concrete innovation can be achieved through the utilization of waste materials, such as sawdust, along with the addition of chemical admixtures to improve performance. This study aims to analyze the effect of sawdust treated through water immersion and oven drying, as well as the addition of Bestmittel admixture, on the workability and compressive strength of concrete. The sawdust variations used were 1 percent, 3 percent, and 5 percent of the cement weight, while Bestmittel was added at 0.5 percent. The research method employed an experimental laboratory approach involving slump tests, absorption tests, and compressive strength tests at 28 days. The results indicate that the variation containing 3 percent oven-dried sawdust provided the optimum performance in terms of both workability and compressive strength. The addition of sawdust above 3 percent tended to reduce compressive strength due to increased porosity. Therefore, the use of sawdust together with Bestmittel in appropriate proportions can improve concrete quality while simultaneously supporting sustainable waste management.